ANALISA LAYANAN RITEL KONVENSIONAL DALAM MENGHADAPI PPKM DIMASA PANDEMI COVID 19 - Dikdik Purwadisastra; Elan Rusnendar (LPPM UNIBI, 2021)
This study aims to see how respondents respond to conventional retail stores during the Covid 19 pandemic, especially after Emergency PPKM and PPKM levels one to four, the method used in this study is qualitative with a descriptive approach to population in this study is not limited because people living in Indonesia who are visiting conventional retail stores while the sampling technique is accidental sampling, it is known that there are 100 respondents, the results obtained are that the majority of respondents rarely shop at conventional retail stores due to several factors, including security that is not guaranteed, especially during the covid 19 pandemic, comfort is also still lacking. not comfortable and of course the variety of products that are still inferior to the marketplace or online retail. The solution is that conventional retailers must continue to improve the service system, for example serving pick-up and delivery of consumer goods by ordering via social media with free shipping for a limited kilometer radius, as well as adding a variety of goods that are still considered limited by consumers.